Cardio-ankle vascular index in subjects with dyslipidaemia and other cardiovascular risk factors - Soska, Vladimir; Frantisova, Michaela; Dobsak, Petr; Dusek, Ladislav; Jarkovsky, Jiri; Novakova, Marie; Shirai, Kohji; Fajkusova, Lenka; Freiberger, Tomas (Journal of atherosclerosis and thrombosis, 2013)
AIM: The cardio-ankle vascular index (CAVI) is a novel non-invasive marker of arterial stiffness and atherosclerosis. The aim of this work was to examine whether the CAVI value in patients with dyslipidaemia (DLP) is increased by the presence of other cardiovascular risk factors: hypertension, diabetes mellitus, and smoking. METHODS: A total of 392 subjects with DLP (166 male, 226 female), with a median age of 58.5 and 5-95 percentile range 32.2-73.9 years were examined. CAVI was measured using the VaSera 1500 system. RESULTS: CAVI correlated significantly with age (p<0.001) and both systolic (p<0.001) and diastolic (p=0.002) blood pressure; higher values were found in men (p=0.034) than in women in the 56-65 age group. There was no significant difference in CAVI between smokers and non-smokers (p= 0.217) and between subjects with and without diabetes mellitus (p= 0.424). CAVI was significantly higher in subjects with hypertension than in the normotensive group (p<0.001) and in statin-treated subjects than in those without statins (p<0.001); however, CAVI values adjusted for age and sex did not differ significantly between these groups. Adjusted CAVI values were higher only in smokers than in non-smokers (former smokers) (p<0.001). CONCLUSION: The study proves conclusively that the CAVI value in DLP patients is not significantly affected by hypertension and diabetes mellitus, but it is increased by smoking.
Keywords: kardiovaskulární nemoci; Humans; lidé středního věku; Risk Factors; Female; rizikové faktory; Aged; dospělí; dyslipidemie; lipidy; ateroskleróza; senioři; lidé; Ankle; Adult; ženské pohlaví; Cardiovascular Diseases; krevní tlak; Male; Atherosclerosis; Middle Aged; kotník; Heart; Lipids; Dyslipidemias; Vascular Stiffness; mužské pohlaví; Blood Pressure; srdce; tuhost cévní stěny